The new fire war, peace, and Democracy in the age of AI - Buchanan, Ben; Imbrie, Andrew (The MIT Press, 2022)
"Is AI a force for ill or for good? How does it work? This book analyzes the potential of AI in many sectors, including global security"--
Keywords: Sicherheitspolitik; Künstliche Intelligenz; Artificial intelligence